Regulation of PD-L1 expression in non–small cell lung cancer by interleukin-1β - Hirayama, Aiko; Tanaka, Kentaro; Tsutsumi, Hirono; Nakanishi, Takayuki; Yamashita, Sho; Mizusaki, Shun; Ishii, Yumiko; Ota, Keiichi; Yoneshima, Yasuto; Iwama, Eiji; Okamoto, Isamu (Frontiers in Immunology, 2023)
Introduction: Programmed cell death-ligand 1 (PD-L1) is a biomarker for prediction of the clinical efficacy of immune checkpoint inhibitors in various cancer types. The role of cytokines in regulation of PD-L1 expression in tumor cells has not been fully characterized, however. Here we show that interleukin-1β (IL-1β) plays a key role in regulation of PD-L1 expression in non-small cell lung cancer (NSCLC).We performed comprehensive screening of cytokine gene expression in NSCLC tissue using available single-cell RNA-Sequence data. Then we examined the role of IL-1β in vitro to elucidate its induction of PD-L1 on NSCLC cells.The IL-1β gene is highly expressed in the tumor microenvironment, particularly in macrophages. The combination of IL-1β and interferon-γ (IFN-γ) induced a synergistic increase in PD-L1 expression in NSCLC cell lines. IL-1β and IFN-γ also cooperatively activated mitogenactivated protein kinase (MAPK) signaling and promoted the binding of downstream transcription factors to the PD-L1 gene promoter. Furthermore, inhibitors of MAPK signaling blocked upregulation of PD-L1 by IL-1β and IFN-γ.Discussion: Our study reports high levels of IL-1β in the tumor microenvironment may cooperate with IFN-γ to induce maximal PD-L1 expression in tumor cells via activation of MAPK signaling, with the IL-1β-MAPK axis being a promising therapeutic target for attenuation of PD-L1-mediated suppression of antitumor immunity.